How a Mediating Variable Need in the Loyalty Examination? - Pambudi, Bima Andrianto; Soliha, Euis; Tjahjaningsih, Endang (Department of Management, Faculty of Economics, Universitas Negeri Semarang, 2018)
The aim of this study was to analyze the effect of bank image and service quality to satisfaction and their impacts on customer loyalty. The object of this research was Bima saving customers at PT. Bank Pembangunan Daerah Jawa Tengah, Klaten Branch. In this study the population used was limited to the customers of the Bima Savings at PT Bank Pembangunan Daerah Jawa Tengah, Klaten Branch. The sample was 97 respondents with the sampling technique of Purposive.The samples were carefully selected so that they were relevant to the study. The results of the research indicate that: bank image has positive significant effect on satisfaction; service quality has positive significant effect on satisfaction; bank image has positive significant effect on loyalty; service quality has positive significant effect on loyalty and satisfaction has positive significant effect on loyalty. The results of mediation effect show that bank image and service quality more effectively influence directly on customer loyalty than through customer satisfaction. Satisfaction is significantly capable as a mediator in the association.Ã‚Â